A Learning Proposal Based on a Project and Collaborative Work: An Online Course Experience - Gabriela Cenich; Graciela Santos (Universidad Autónoma de Baja California, 2005)
One of the basic necessities for education in the future is to prepare learners to participate in a computer network, since in the information society knowledge is the most critical resource for social and economic development. This paper addresses how project-based learning was designed and implemented in a course on computer science at the National University of Central Argentina. The objective of the course was to engage students in the production of projects that were authentic, meaningful, and intended for future teaching and professional use. Two types of interaction have been considered in computer-mediated learning: individual interaction (interaction with the content), and social or interpersonal interaction. This paper describes the course design, provides an overview of the processes involved in developing the project-based learning activities, and reports the responses of students to the course.